Intravascular extension of Wilms tumor: Characteristics of tumor thrombus and their impact on outcomes. Issue 1 (February 2021) - Qureshi, Sajid S.; Bhagat, Monica; Smriti, Vasundhara; Murli, Divya; Baheti, Akshay; Yadav, Subhash; Prasad, Maya; Khanna, Nehal; Laskar, Siddharth; Kembhavi, Seema A.; Vora, Tushar; Chinnaswamy, Girish; et al.
Summary: Background: Studies describing intravascular involvement in Wilms tumor have focused on illustrating individual institutional experience and the elements of surgical management. Thrombus characteristics like extent, patterns of regression, and correlation with the surgical findings, intraluminal adhesion, and viable tumor in the thrombus, and patency of the inferior vena cava (IVC) have not been systematically described. Objectives: The aim of this study is to evaluate these thrombus characteristics and explore their impact on the overall outcomes. Methods: All patients with histologically confirmed Wilms tumors with intravascular thrombus diagnosed in the pediatric oncology unit of Tata Memorial Hospital registered from 2006 to 2019 were included. Data regarding clinical, radiological, and surgical particulars were retrieved from the prospectively maintained institutional database. Specific data for the thrombus included: distal extent before and after neoadjuvant chemotherapy, correlation of extent with the surgical findings, completeness of thrombectomy, the presence of a viable tumor in the thrombus, and the patency of the IVC. Survival analysis was performed utilizing the Kaplan–Meier method on SPSS software version 25. Results: The study included 43 (9.9%) of the 432 patients with Wilms tumor having intravascular extension. Retrohepatic IVC (33.3%) followed by atrioventricular (26%) formed the frequent levels of thrombus with maximum regression occurring after chemotherapy in the latter (Summary figure). The overall concordance rate between computed tomography (CT) scan and surgical findings for the presence of thrombus was 86% and 4 patients had the thrombus limited to a lower level than the preoperative scan. At a median follow-up of 5-years, the 5-year event-free and overall survival was 81% and 82.2% respectively. Atrioventricular thrombus ( p  = 0.003) and postoperative patency of IVC ( p  = 0.02) were significantly associated with inferior survival, while the extent of regression, thrombus fracture, and viability was not significant. Discussion: The findings of this study bring forth the characteristics of intravascular tumor thrombus affecting the outcomes which can be validated in future prospective studies. Although the ideal method for radiological assessment of the intravascular thrombus is elusive, CT scan provided adequate information for the presence and level of the intravascular thrombus with reasonable accuracy in this study. Study limitations include small sample size, the limited number of events, and lack of multivariate analysis to rule out confounding factors that could influence the observed findings. Conclusion: Atrioventricular thrombus and occlusion of IVC represent adverse prognostic factors. The extent of regression, fracture, and viability of thrombus did not affect survival in this study. Summary fig. A collage of axial, coronal and sagittal computed tomogram images showing retrohepatic [A and A1], atrial [B and B1], ventricular [C and C1] thrombus. Summary figure